Answer:
f(2) = -6
Step-by-step explanation:
f(x) = 3x - 12
Let x =2
f(2) = 3*2 -12
= 6-12
= -6
Answer:
Step-by-step explanation:
When working with 45-45-90 triangles the hypotenuse is the same as the other legs multiplied by root 2. Therefore if you need to find the legs and already have the hypotenuse, divide the hypotenuse by root 2.
10/ sqrt(2) = 7.1 is the rounded answer.
to double check your work just multiply 7.1 by the square root of 2 and you'll get <em>close</em> to 10. (because the answer is rounded and not exact.)
Answer:
Step-by-step explanation:
The second one.
The sum of the terms of a geometric sequence with common ratio lesser than 1 is calculated through the equation,
Sn = (a1) x (1 - r^n) / (1 - r)
Substituting the known values,
S5 = (6) x (1 - (1/3)^5) / (1 - 1/3) = 242/27
Thus, the sum of the first five terms is approximately equal to 8.96.
Answer:
B plz mrk brainliest
Step-by-step explanation: